Foreigners and their food : constructing otherness in Jewish, Christian, and Islamic law - Freidenreich, David M., 1977- (Berkeley : University of California Press, 2011)
Foreigners and Their Food explores how Jews, Christians, and Muslims conceptualize'us' and'them' through rules about the preparation of food by adherents of other religions and the act of eating with such outsiders. David M. Freidenreich analyzes the significance of food to religious formation, elucidating the ways ancient and medieval scholars use food restrictions to think about the'other.' Freidenreich illuminates the subtly different ways Jews, Christians, and Muslims perceive themselves, and he demonstrates how these distinctive self-conceptions shape ideas about religious foreigners and communal boundaries. This work, the first to analyze change over time across the legal literatures of Judaism, Christianity, and Islam, makes pathbreaking contributions to the history of interreligious intolerance and to the comparative study of religion.
Part I. Introduction : Imagining Otherness : -- 1. Good fences make good neighbors -- 2.'A people made holy to the Lord' : meals, meat, and the nature of Israel's holiness in the Hebrew Bible -- Part II. Jewish Sources on Foreign Food Restrictions : Marking Otherness : -- 3.'They kept themselves apart in the matter of food' : the nature and significance of Hellenistic Jewish food practices -- 4.'These Gentile items are prohibited' : the foodstuffs of foreigners in early rabbinic literature -- 5.'How nice is this bread!' : intersections of Talmudic scholasticism and foreign food restrictions -- Part III. Christian Sources on Foreign Food Restrictions : Defining Otherness : -- 6.'No distinction between Jew and Greek' : the roles of food in defining the Christ-believing community -- 7.'Be on your guard against food offered to idols' :'eid$1!;5(Bothuton' and early Christian identity -- 8.'How could their food not be impure?' : Jewish food and the definitions of Christianity -- Part IV. Islamic Sources on Foreign Food Restrictions : Relativizing Otherness : -- 9.'Eat the permitted and good foods God has given you' : relativizing communities in theQur'an -- 10.''Their food' means their meat' : Sunni discourse on non-Muslim acts of animal slaughter -- 11.'Only monotheists may be entrusted with slaughter' : the targets of Shi$1#O,(Boreign food restrictions -- Part IV. Comparative Case Studies : Engaging Otherness : -- 12.'Jewish food' : the imnplications of medieval Islamic and Christian debates about the definition of Judaism -- 13. Christians'adhere to God's book,' but Muslims'Judaize' : Islamic and Christian classifications of one another -- 14.'Idolaters who do not engage in idolatry' : rabbinic discourse about Muslims, Christians, and wines
Includes bibliographical references and indexes.
Keywords: Food -- Religious aspects -- Comparative studies; Identification (Religion) -- Comparative studies; Religions -- Relations; Jews -- Dietary laws; Muslims -- Dietary laws; Food -- Religious aspects -- Christianity